Promoting thinking skills through interactive character learning model (ICLM) – Chinese character learning using WhatsApp for Malay L3 learners - Chu, Hong Heng; Toh, Ling Ling (Journal of Modern Languages, 2017)
Chinese characters are known as ideographs and this system of writing differs totally with the system of writing of Malay L3 learners’ first and second languages. Since each Chinese character depicts a strong association between its sound, shape and meaning, the character writing hence involves a series of mental processes. Owing to this unique feature, Malay L3 learners need to struggle through the process of writing as they need to remember not only the shape of any character, but also its sound and meaning. In this research, we try to use ICLM to facilitate the learning of Chinese characters for Malay L3 learners and hence help them to recognize the Chinese characters more effectively besides making the process of learning more interesting and therefore, analysing its results. Through analysis, we found that Malay L3 learners shown more interest and gave faster responses in sentence making. Their ability in recognizing the correct characters and making sentences also increased following the introduction of ICLM.